Guidelines for the Development of Straw Mushroom Cultivation Groups in Ban Chang Community, Chang Yai Subdistrict, Bang Sai District, Phra Nakhon Si Ayutthaya Province - Promnakon, Kanoknat (RMUTL Journal of Socially Engaged Scholarship, 2024)
Guidelines for the development of straw mushroom cultivation groups in Ban Chang Community, Chang Yai Subdistrict, Bang Sai District, Phra Nakhon Si Ayutthaya Province. The objectives of this study were to study the guidelines for the development of straw mushroom cultivation groups and the establishment of straw mushroom cultivation groups with the following methods: 1) study and survey the area context, 2) knowledge transfering through community participation workshops, and 3) evaluate the results of operations. The result of the analysis of the development approach and the evaluation of the potential of the local context together with the community, the researcher and the local wise found that the community needs to develop a career for straw mushroom cultivation from the residue after harvesting rice. Resulting in the establishment of the Ban Chang straw mushroom cultivation group as an extra-job. The researcher, together with the local sages of the community, passed on the knowledge to the community from the process of using the leftover raw material after harvesting rice, rice straw, as the main raw material for cultivation of straw mushrooms. The group members were increased by 84% from 4 members to 25 members, which led to a place to grow straw mushrooms for Ban Chang as a model in the community. And 100 % satisfaction with the performance results in sales of straw mushrooms increasing 85 % per month from 3,000 baht to 20,000 baht, increasing the value of agricultural products from the leftovers after harvest and the group has managed by your own group for the distribution of income to the community market, and create jobs and generate income for the community.